2011
DOI: 10.1016/j.jecp.2011.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Social information processing in preschool children: Relations to sociodemographic risk and problem behavior

Abstract: Using a multi-component, process-oriented approach, the links between Social Information Processing in the preschool years and a) sociodemographic risk, and b) behavior problems in preschool, were examined in a community sample of 196 children. Findings provided support for our initial hypotheses that aspects of social information processing in preschool are related to both sociodemographic risk and to behavior problems in preschool. Response evaluation, and in particular, the positive evaluation of an aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 60 publications
2
61
0
4
Order By: Relevance
“…SIP was measured with The Social Information Processing Interview – Preschool Version (SIPI-P; Ziv & Sorongon, 2011). This is a 20-minute long structured interview depicting a series of vignettes in which a protagonist is either being rejected by two other peers (in the “ peer-rejection ” vignette) or provoked by another peer (in the “ peer-provocation ” vignette).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…SIP was measured with The Social Information Processing Interview – Preschool Version (SIPI-P; Ziv & Sorongon, 2011). This is a 20-minute long structured interview depicting a series of vignettes in which a protagonist is either being rejected by two other peers (in the “ peer-rejection ” vignette) or provoked by another peer (in the “ peer-provocation ” vignette).…”
Section: Methodsmentioning
confidence: 99%
“…Pettit, Harrist, Bates, & Dodge (1991), have reported that preschoolers’ outcome expectations regarding aggressive and competent responses were predicted by the quality of their relationship with their parents. In more recent studies, Runions and Keating (2007) have shown that hostile attribution measured during the preschool years is a better predictor of problem behavior in first grade than hostile attribution measured concurrently in first grade, and Ziv and Sorongon (2011) have shown that children with aggressive tendencies evaluate more beneficial social and interpersonal outcomes for aggressive responses. As opposed to the above studies, Pettit, Brown, Mize, and Lindsey (1998) have reported that preschool children failed to distinguish between hostile and non-hostile intents and almost always report provocateurs to have hostile intent.…”
Section: Social Information Processing In Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between children's social information processing (SIP) patterns and their social skills has been well established in many studies, especially in school (e.g., Crick & Dodge, 1994; Dodge, 1986; Dodge, Bates, & Pettit, 1990; Dodge, Laird, Lochman, & Zelli, 2002; Dodge & Price, 1994; Garner & Lemerise, 2007; Lansford et al, 2006; Schultz, Izard, & Bear, 2004; Zelli & Dodge, 1999) but also in the preschool years (e.g., Hart, DeWolf, & Burts, 1992; Katsurada & Sguwara, 1998; Runions & Keating, 2007; Ziv & Sorongon, 2011). Most of these studies have linked distorted SIP patterns with less competent social skills, but some (e.g., Mayeux & Cillessen, 2003; Nelson & Crick, 1999), have also reported strong links between more competent social information processing patterns and prosocial behavior.…”
Section: Social Information Processing Patterns Social Skills and Smentioning
confidence: 99%
“…The SIP training session used two sets of materials: stories illustrating social situations with bears from the "Social Information Processing Interview for Pre-schoolers" (SIPI-P, Ziv & Sorongon, 2011) and video-based SIP illustrating social situations from the "Schultz Test of Emotion Processing-Preliminary Version" (STEP-P, Schultz et al, 2010).…”
Section: Sip Training Experimental Groupmentioning
confidence: 99%